Clinical Ethics Training in Canada: Moving Towards Standardization - Badaiki, Winifred; Frolic, Andrea (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
This paper summarizes the presentation and stakeholder feedback gathered from the Canadian Bioethics Society Workshop and Community Forum in May 2023, in a session entitled, “Clinical Ethics Fellowship in Canada: Making the Move Towards Standardization”. This summary provides insight into the clinical ethics fellowship landscape across Canada, including current gaps in the training of Canadian healthcare ethicists and opportunities to advance the journey towards standardization.